A mutant allele uncouples the brassinosteroid-dependent and independent functions of Brassinosteroid Insensitive 1 - Holzwart, Eleonore; Wanke, Friederike; Glöckner, Nina; Höfte, Herman; Harter, Klaus; Wolf, Sebastian (Plant physiology, 2020)
Plants depend on various cell surface receptors to integrate extracellular signals with developmental programs. One of the best-studied receptors is BRASSINOSTEROID INSENSITIVE 1 (BRI1) in Arabidopsis (Arabidopsis thaliana). Upon binding of its hormone ligands, BRI1 forms a complex with a shape-complementary coreceptor and initiates a signal transduction cascade, which leads to a variety of responses. At the macroscopic level, brassinosteroid (BR) biosynthetic and receptor mutants have similar growth defects, which initially led to the assumption that the signaling pathways were largely linear. However, recent evidence suggests that BR signaling is interconnected with several other pathways through various mechanisms. We recently described that feedback from the cell wall is integrated at the level of the receptor complex through interaction with RECEPTOR-LIKE PROTEIN 44 (RLP44). Moreover, BRI1 is required for another function of RLP44: the control of procambial cell fate. Here, we report a BRI1 mutant, bri1cnu4, which differentially affects canonical BR signaling and RLP44 function in the vasculature. Although BR signaling is only mildly impaired, bri1cnu4 mutants show ectopic xylem in place of procambium. Mechanistically, this is explained by an increased association between RLP44 and the mutated BRI1 protein, which prevents the former from acting in vascular cell fate maintenance. Consistent with this, the mild BR response phenotype of bri1cnu4 is a recessive trait, whereas the RLP44-mediated xylem phenotype is semidominant. Our results highlight the complexity of plant plasma membrane receptor function and provide a tool to dissect BR signaling-related roles of BRI1 from its noncanonical functions.